Effectiveness of an online training program for improving nurses' competencies in disaster risk management - Jamileh Farokhzadian; Hojjat Farahmandnia; Asghar Tavan; Gülcan Taskiran Eskici; Faezeh Soltani Goki (BMC, 2023)
Abstract Background Nurses' incompetency in disaster risk management can have many negative consequences during disasters, so it is important to prepare nurses and improve their competencies in disaster risk management. This study was conducted with the aim of investigating the effectiveness of an online training program to improve competencies in disaster risk management. Method This interventional study was conducted on nurses working in a specialized trauma hospital affiliated with the Kerman University of Medical Sciences in southeastern Iran in 2023. Eighty-one nurses were randomly assigned into two interventions (n = 42) and control groups (n = 39). The intervention group received an online training program in four sessions, and both groups electronically completed the demographic questionnaire and the nurses' perceptions of disaster core competencies scale (NPDCC) before and one month after the intervention. Results The study results showed no significant difference in disaster competency scores between the two groups before the intervention (p < 0.51), but the NPDCC score in the intervention group was statistically significant after the intervention compared to before the intervention (p < 0.02) and no statistically significant difference was observed between the two groups after the intervention (p < 0.16). Conclusion While the online training program was found to significantly improve the NPDCC score of nurses in the intervention group, this increase was not significant when compared to the control group. Therefore, we suggest continuous practical exercises and maneuvers to improve nurses' perception of the competencies required for effective disaster management.